Performance comparisons between lightpath and light-tree schemes in dynamic multicast traffic grooming process - Yu, Xiaojun (2013)
To support multicast applications while improving wavelength capacity utilization in wavelength division multiplexing (WDM) networks, dynamic multicast traffic grooming problem has been extensively studied in recent years, and various algorithms using either lightpath or light-tree schemes have been proposed. To the best of our knowledge, however, no systematic comparison has ever been made between the blocking performances of these two different types of schemes. In this paper, we firstly present a brief survey of the various existing algorithms for dynamic multicast traffic grooming, followed by a short discussion on the pros and cons of lightpath and lightp-tree schemes respectively. By conducting extensive numerical simulations, we carefully compare the blocking performances of these two types of schemes. Our study results show that, in most cases, the lightpath-based methods outperform the light-tree based ones, typically with only a slightly higher consumption of O/E/O resources. We provide an explanation to such interesting observations. Effects of the ratio of multicast traffic to overall network traffic and the average number of destinations of each multicast request are also studied.